The role of Perilipin 5 in pathological myocardial remodeling - Dunzhu, Danzeng; Han, Gao; Shanshan, Qin; Li, Shangshi; Yang, Jiali; He, Jian; Gou, Siyu; Dong, Gang; Jiang, Chunrong; Hou, Jun (Frontiers in Pharmacology, 2025)
Pathological cardiac remodeling (REM), caused by various pathological factors and characterized by changes in cardiac structure and geometry, is strongly associated with heart failure (HF). It damages cardiac tissue, alters energy metabolism, increases oxidative stress, and cause matrix metalloproteinase activation, cardiomyocyte hypertrophy, and interstitial fibrosis, leading to HF. REM determines the outcome of cardiovascular disease. Current treatments have limitations. REM is associated with cardiac energetic remodeling, and modulation of metabolic substrates may slow down the disease. Perilipin 5 (Plin5), positioned as a structural protein located on the surface of lipid droplets (LDs), is abundant in tissues and cells that rely on mitochondrial β-oxidation for energy production. It is the most recently identified member of the perilipin protein (PAT) family, with a notable enrichment in the cardiac muscle. Emerging evidence highlights the critical role of intracellular LD in the regulation of energy metabolism, with metabolic disruptions of LD being directly correlated with the incidence of metabolic disease. As a key barrier to LD, Plin5 is instrumental in controlling the catabolism of LD and regulating the metabolism and transport of fatty acids (FAs). As a protectant against excessive β-oxidation of free fatty acids (FFAs), Plin5 acts to isolate and neutralize overly oxidized fatty acids, thereby shielding the heart from myocardial remodeling instigated by a variety of etiological factors. This protective mechanism helps to ameliorate the progression of persistent and detrimental myocardial remodeling, which can otherwise lead to the development of severe heart failure. This systematic review attempts to delineate the metabolic disorders associated with pathological cardiac remodeling, focusing on the properties and regulatory mechanisms of Plin5. By synthesising current literature, it investigates the pivotal role of Plin5 in modulating the distinctive attributes, initiating factors, and molecular signaling networks underpinning pathological cardiac remodeling.